Detection of shallow wall-thinning of pipes using a flexible interdigital transducer-based scanning laser Doppler vibrometer. (November 2022) - Kang, To; Han, Seong-Jin; Han, Soonwoo; Kim, Kyung-Mo; Kim, Dong-Jin
Interdigital transducer (IDT)-based scanning laser Doppler vibrometers (SLDVs) have recently been developed to detect shallow defects in plates. An IDT-based SLDV was augmented with Lamb wave frequency fusion capability to enable the imaging of defects across the entire depth of a plate. Dry-coupled IDTs are a type of field-deployable IDT that do not require the attachment of a couplant to the structure. However, this technique is not applicable to the analysis of shallow wall thinning, because IDTs composed of lead zirconium titanate (PZT) cannot be attached to the curved surface of a structure. To address this issue, we developed a new type of IDT—the flexible IDT—that can be bent along the circumferential direction of a pipe. To set the gap spacing of the flexible IDT, the wavenumber sensitivity and minimum distance from the reference mode (MDRM) was calculated, and the S 0 mode is selected to ensure high-wavenumber sensitivity above the threshold of the MDRM. The proposed flexible IDT-based SLDV was tested by using it to visualize the wall thinning on pipes with 4%, 6%, and 20% thinning. The results of this study will contribute toward the development of systems that improve on existing planar laser scanning schemes and enable shallow defect detection in pipes using laser ultrasonics.